The unity of training, education and health of preschool children in the process of training in karate - Bodnar Ivanna Romanovna; Vitos Yaroslav Kazimirovich (Kharkov National Pedagogical University, 2011)
The literature were analyzed and syntheses. Theoretically proved the possibility of solving complex educational, recreational and educational objectives of physical education of children by means of karate. Found that the use of breathing exercises, exercises of sports and dance character helps to improve physical and mental development of children. It is proved that karate training improves the cardiovascular and respiratory systems, blood system and contribute to the formation of a correct posture, hardening, increase the level of coordination, flexibility, strength and speed.